Pelatihan Pembuatan Fun Games bagi Guru PAUD di Kabupaten Jombang Jawa Timur - Mallevi Agustin Ningrum; Eka Cahya Maulidiyah; Nurul Khotimah (Universitas Mathla'ul Anwar Banten, 2020)
FUN GAMES MAKING TRAINING FOR EARLY CHILDHOOD EDUCATION TEACHERS IN JOMBANG REGENCY, EAST JAVA. The purpose of this training is to develop teacher skills and knowledge in making fun games that are in accordance with the characteristics and strengths that exist in PAUD institutions. The method used in the implementation of this service is to use lecture, question and answer, discussion, direct instruction, and projects in the form of the practice of making fun games for young children. The practice will be evaluated together by presenters and peers from other PAUD institutions to get constructive input and suggestions for implementation in PAUD institutions that are managed by each. The time needed in this community service program starts from the design, implementation and report preparation stages for 6 months. The report on the community service program will later be completed with certificates for training participants, participant questionnaires, and evidence of the implementation of activities. The service report will also be followed up by making scientific articles and ISBN training books. The results of the service program aimed at PAUD teachers are that teachers are able to make fun games that have novelty values ​​and are in accordance with the characteristics of child development and the characteristics of PAUD. The results of the implementation of the community service program show a significant impact. This is evident from the results of the work on the pretest and posttest of the training participants who achieved improvements before and after the community service program was implemented.